Karakterisasi Kekuatan Tarik Komposit Hybrid Lamina Serat Anyam Sisal dan Gelas Diperkuat Polyester - Yudhanto, Ferriawan; Sudarisman, Sudarisman; Ridlwan, M. (Semesta Teknika, 2016)
Hybrid fiber composite is a combination of two or more types of fiber that can be based on the architecture or type of the reinforcement. In this study, smoothly spun agave sisalana and cotton yarn were woven to produce sisal-cotton hybrid fabric . The sisal-cotton hybrid fabric (S) was combined with woven glass fabric (FG) to produce hybrid fiber reinforcing system. Four variations of hybrid fiber reinforcement, i.e. three layers of woven glass fabric (FG-FG-FG), glass-sisal-glass fabrics (FG-S-FG), sisal-glass-sisal fabrics (S-FG-S), and three layers of woven sisal-cotton fabric (S-S-S), each embedded in polyester resin were fabricated using cold press mold method. It was expected that the hybrid fiber composite exhibited new properties derived from both types of fiber so that the advantages of each fiber type would appear on the mechanical properties of the hybrid composite systems. The properties being evaluted were tensile properties and density. The results showed that the highest tensile strength of the hybrid systems (FG-S-FG: 117 MPa) is a combination of those of both types of reinforcement, tend to obey the rule of mixtures, i.e. higher than that of natural fiber composite (S-S-S: 48 MPa) but lower than that of glass fiber composite (FG-FG-FG: 133 MPa). Tensile strain-to-failure was noted being sharply increase from 0.33% for GFRP composit up to above 1.07% by replacing the middle layer of FG reinforcement with S reinforcement. Whilst the density of the S-FG-S hybrid system seems to obey the rule of mixtures, that of the FG-S-FG hybrid system was observed lower than expected. This may due to the resin requires longer time to wetthe fibers so that the air between fibers did not posses enought time to evacuate at the jell time being reached such that producing void leading to lowering the density.